Sensitivity Analysis of Finite Volume Simulations of a Breaking Dam Problem - Cruchaga-Ssa., M (Emerald Group Holdings Ltd., 2015)
Purpose - The present work is a numerical study of a breaking dam problem. The purpose of this paper is to assess the effect of turbulence and surface tension models in the prediction of the interface position in a long-term analysis. Additionally, dimensional effects are analyzed by carrying out both 2D and 3D simulations. Design/methodology/approach - Finite volume simulations performed with the different models are compared between them and contrasted with numerical results computed using other numerical techniques and experimental data. Findings - The reported numerical results are in general in good agreement with experimental results available in the literature. They are also consistent with numerical solutions of other authors obtained using different numerical techniques. The results show that the laminar simulations exhibit strong mesh size dependency, while the turbulence models seem to help in producing mesh-independent solutions. Surface tension modeling does not seem to play a relevant role in the interface evolution. Practical implications - Model validation. Originality/value - The value of the present work encompass the comparison of different flow conditions used to simulate a free surface problem and their validation by contrasting numerical results with experiments. Also, the results shown in the present work are a contribution to the understanding of the role of some specific aspects of the models in the simulation of the proposed problem. © Emerald Group Publishing Limited.